Vocational training and moral judgment - are there gender-specific traits among apprentices in commercial business? - Lüdecke-Plümer, Sigrid [Verfasser]; Zirkel, Andrea [Verfasser]; Beck, Klaus [Verfasser] (My University, 1997)
"Since Carol Gilligan (1982) presented her conception of 'two morals', several empirical studies have been carried out to verify her assumption that the moral reasoning of men and women generally follows different principles. Some of the research findings occasioned us to look for gender-specific traits in a sample of insurance apprentices as well. Once again, the data confirm that Gilligan's assumption cannot be uphold although some results of our detailed analysis of moral reasoning and the conditions of its development seem to be gender-biased. In our paper we argue that gender differences in moral judgments should not be dealt with as a matter of the quality of moral reasoning ('different voice-hypothesis') but rather as a matter of perceiving social role concepts in a deciding situation ('different role-hypothesis'). Thus, the intra- and interpersonal differences in moral judgment found in our study might not be explained by the internal structure 'moral competence' alone. To a certain extent they are also caused by the interaction between the social situation, the individual's personal and moral self and moral competence." (Autorenreferat, BIBB-Doku)
Keywords: G 2.4.2 Lebenskonzepte, -stile, Werte; P 2.3 Auszubildende; S 6.4.1 Kaufleute; G 2.4.5 Gender Mainstreaming; Berufsethos; Moral; Auszubildender; Kaufmännischer Beruf; Geschlechtsspezifische Faktoren; Sozialkompetenz; Sozialisationsbedingungen; Quantitative Angaben